Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I know $y=f(x)$ is differentiable and invertible.

His inverse function is $x=g(y)$ which is also differentiable.

I have to prove that $g'(y)= 1/(f'(x))$.

I tried first with an baby example with $y=x^2$ and it turned out that this holds.

But I have no idea on how to prove this. Please provide some help!

share|cite|improve this question
up vote 3 down vote accepted

The correct equality is rather $g'(x)=1/f'(g(x))$.

Hint: Write $f \circ g= \operatorname{Id}$ and use the chain rule.

share|cite|improve this answer
Can you please be a bit more specific? – Sjoerd Smaal Feb 16 '13 at 13:49
@SjoerdSmaal: You only have to write $f(g(x))=x$ and then to differentiate the equality. – Seirios Feb 16 '13 at 13:52

Directly by definition, and putting $\,f(y)=x\Longleftrightarrow y= f^{-1}(x)=g(x)\,$:

$$g'(x_0):=\lim_{x\to x_0}\frac{g(x)-g(x_0)}{x-x_0}=\lim_{x\to x_0}\frac{y-y_0}{f(y)-f(y_0)}=\lim_{y\to y_0}\frac{1}{\frac{f(y)-f(y_0)}{y-y_0}}=\ldots$$

Now, you have to talk, perhaps, a little about the cases:

1) $\,f(y)=f(y_0)\,$ , a constant function in some neighborhood of $\,y_0\,$...but this is impossible (why?)

2) We have $\,x\to x_0\Longrightarrow g(x)=y\to g(x_0)=y_0\,$ (why?)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.